Study of Low-Frequency Electromagnetic Ion-Cyclotron Wave for Ring Distribution in Magnetosphere of Saturn - Haridas , Annex Edappattu; Pandey, Rama Shankar (Trends in Sciences, 2022)
Magnetic cyclotron waves were discovered by the Cassini-Huygens spacecraft in Saturn's atmospheric torus’ magnetic layer. They are left-handed and propagate at a minor angle to the ambient magnetic field in most areas because their frequency is close to the frequency of the aqua ions. The ion cyclotron instability caused by Saturn's neutral cloud ions helps explain their formation. They can be classified as n = 2 mode fluctuations because of the ion-ring distribution. We planned the characteristics of these waves in advance of starting this project. Our dispersion growth rates are evaluated using kinetic method analysis as well. The results were calculated and explained for the exemplary values of the magnetosphere parameters suitable for Saturn. Another potential free energy source for ion cyclotrons is temperature anisotropy. Instead of the standard Maxwell distribution, a ring distribution is employed in this study. The focus of this research is EMIC waves’ oblique propagation in the magnetic field, which changes their temperature anisotropy, ion energy density, and propagation angle. The interaction of relativistic particles with ion cyclotron waves is also included in this extension. EMIC wave size decreases with the increasing density of particles, as shown by a numerical study. A comparison of planetary studies based on data from space plasma environments and magnetospheric systems produced these results. HIGHLIGHTS Temperature anisotropy - free energy source for Ion Cyclotron waves EMIC wave size decreases with the increasing density of particles Saturn's neutral cloud ions helps the formation of ion cyclotron instability GRAPHICAL ABSTRACT